(3ajV GdaJGM Ydi fhQ GdCbGMs - (3SjO YHO Gddg Hf GdMGL EHQGgje GdYdhjs ((3ehQJjGfjG s)
(3ChdgG (B:s
(3fGbUI GdChd hjHOC GdehLhO ajg Hbhdg (B: (3hjZdH GdJNUjU ai PG GdHGH jYfi Cf GdJNUjU eSJaGO ZGdHkG ai PG GdHGH Ci HGH JbOje eG Mbg GdJCNjQ ai bhdg JYGdi (B" (3EjGc fYHO hEjGc fSJYjf (B" s
(3BNQgG (B:s
(3hjLYdg HeG ajg ef HjGf CSQGQ GdbQBf GdeHjf hUdI HSjO GdeQSdjf ai GdOfjG hGdBNQI Bejf hMSHfG Gddg hfYe Gdhcjd hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eYfhfI HGdMHQ GdCMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs